Metronidazole Research: Historical Developments and Future Directions - Elathram, Sondos Fouzi; Abdelrahman, Riad Mohammed; Ali, Zinab Salah; Arbab, Ismail Adam; Suliman, Mohsen Hussein; Abdelgadir, Ala Gamaleldin; Ahmed, Eltieb Omer; Gasmallah, Sahar Ibrahim; Ahmed, Wafaa Ramadan; Fadul, Khalid Hamid; Jalal, Mohammed; Mgbechidinma, Chiamaka Linda; et al. (British Journal of Healthcare and Medical Research, 2026)
Metronidazole is widely used around the world to treat anaerobic, parasitic, and bacterial infections. Yet, despite its significance, a comprehensive review that weaves together its historical Breakthroughs and charts a course for future research is still missing. This study used bibliometric analysis to comprehensively examine the global landscape of Metronidazole research, based on publications from the Scopus database between 1960 and 2024. Data were analyzed using R software, VOS viewer, and Cite Space to explore qualitative and quantitative trends. Results: The first article published in 1960, the number of scientific publications has increased, especially after 1985. 6,172 publications were identified with 160,000 citations, showing a steady annual growth rate of 6.26%, reflecting a vibrant and steadily growing field. Notably, publication rates soared after 2024. WANG was the most prolific author, while China and the United States led in productivity, with 13% international collaboration. The Journal of Antimicrobial Chemotherapy is the leading journal in terms of publication venue. Network analysis spotlighted Metronidazole, tetracycline, and vancomycin as central antibiotics. Highly cited studies focused on Clostridium difficile infection, Helicobacter pylori eradication, and bacterial vaginosis. Over time, research themes have shifted from traditional pharmacology and microbiology to innovative areas such as nanotechnology, biosensing, computational modeling, and green chemistry. The research on Metronidazole shifting into four promising directions for future exploration: harnessing artificial intelligence to predict resistance, leveraging computational tools to uncover new applications, embracing green chemistry to minimize environmental impact, and advancing precision medicine through genetic biomarkers.